2020
DOI: 10.3390/ijerph17197299
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polish Wild Mushrooms as Beta-Glucan Sources

Abstract: Mushroom beta-glucans show immunomodulatory, anticancer and antioxidant features. Numerous papers have been published in the last years on fungal polysaccharides, especially beta-glucans, demonstrating their various biological activities. However substantial data about beta-glucan contents in many mushroom species, especially wild mushrooms, are still missing. Therefore, the main objective of the study was to evaluate β-glucans in 18 species of wild mushrooms and three species of commercial mushrooms for compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 83 publications
(196 reference statements)
0
23
0
Order By: Relevance
“…The β-glucan content in different cultivars of Lentinula edodes , determined by a specific kit (Megazyme International, Ireland), ranged from 20 to 40% and from 33 to 58%, respectively, in the pileus and the stipe regions of the dried fruiting bodies [ 63 ]; these values of β-glucan content were confirmed by two subsequent studies detecting β-glucans in a large number of fruiting bodies of wild and commercial edible mushroom species, including the Lentinula edodes [ 64 , 65 ]. The latter study assayed β-glucans also with the Congo red method, which detects the β-glucans with a triple-helix chain conformation, possibly characterized by more efficient immunomodulatory activities [ 10 ].…”
Section: β-Glucans Biological Effectsmentioning
confidence: 95%
See 1 more Smart Citation
“…The β-glucan content in different cultivars of Lentinula edodes , determined by a specific kit (Megazyme International, Ireland), ranged from 20 to 40% and from 33 to 58%, respectively, in the pileus and the stipe regions of the dried fruiting bodies [ 63 ]; these values of β-glucan content were confirmed by two subsequent studies detecting β-glucans in a large number of fruiting bodies of wild and commercial edible mushroom species, including the Lentinula edodes [ 64 , 65 ]. The latter study assayed β-glucans also with the Congo red method, which detects the β-glucans with a triple-helix chain conformation, possibly characterized by more efficient immunomodulatory activities [ 10 ].…”
Section: β-Glucans Biological Effectsmentioning
confidence: 95%
“…Table 1 reports all glucan and β-glucan content in different species and parts of commercially cultivated mushrooms [ 64 ]. The α-glucan content in mushrooms was only a small percentage of total glucans, even less than 1.5% in some Lentinula edodes cultivars [ 63 , 64 , 65 ].…”
Section: β-Glucans Biological Effectsmentioning
confidence: 99%
“…Detailed studies of β-glucans demonstrated their beneficial impact on human life. These compounds are responsible for many bioactivities, such as immunomodulating, anticholesterolemic, antidiabetic, antioxidant, and neuroprotective activities, as well as lipid balance improvement, and they even have a great impact on the general feeling of the consumer [133]. They bind to a membrane receptor and induce these biological responses [134].…”
Section: Macrofungal β-Glucansmentioning
confidence: 99%
“…In an in vitro study conducted by Van Doan et al (2015) , it was noted that Jerusalem artichoke extract at 5% concentration caused maximum growth in the bacterial population of Lactobacillus plantarum , finding that is in line with that of ours. Similarly, the observed increase in the growth of each of the two probiotics cultured together with mushroom extract could be attributed to the prebiotic components, such as chitin, hemicellulose, β- and α-glucans, mannans, xylans, and galatians, which are widely available in mushrooms ( Mirończuk-Chodakowska and Witkowska, 2020 ; Atila et al, 2021 ). The findings from our study are supported by several other studies.…”
Section: Discussionmentioning
confidence: 91%